A highly sensitive and reusable electrochemical mercury biosensor based on tunable vertical single-walled carbon nanotubes and a target recycling strategy. Issue 5 (18th January 2017) - Shi, Lei; Wang, Yan; Chu, Zhenyu; Yin, Yu; Jiang, Danfeng; Luo, Jingyi; Ding, Shiming; Jin, Wanqin
Abstract : Conformational regulation of SAMs was proposed for controlled growth of v-SWCNTs, which were employed to construct a high-performance mercury biosensor using a target recycling strategy. Abstract : In this work, a novel electrochemical Hg 2+ biosensor with high sensitivity and excellent reusability was presented. The sensor was based on tunable vertical single-walled carbon nanotubes (v-SWCNTs) and a target recycling strategy. A facile and scalable approach involving the conformational regulation of self-assembled monolayers was established for the fabrication of v-SWCNTs with tailored orientation and homogeneity. The obtained v-SWCNTs exhibited superior properties including a large specific area, high electrical conductivity, and excellent substrate binding strength, opening up a wide horizon for advanced electrochemical applications. Meanwhile, an efficient Hg 2+ recycling strategy was designed using exonuclease III. In this strategy, a trace amount of Hg 2+ triggered consecutive nicking reactions, and numerous report probes were released to bind with v-SWCNTs through π–π interactions. Based on the innovative design, an ultralow detection limit of 3 fM (S/N = 3), a wide linear range from 10 fM to 1 μM, high selectivity, and good reliability were achieved for a Hg 2+ assay in water and serum samples using the prepared biosensor. Besides, due to the reversibility of π–π interactions, the stable v-SWCNT interface was regenerated for 50 consecutive measurements without obvious signal loss, making it a promising candidate for routine and efficient Hg 2+ monitoring.